Evaluating pellet and meal feeding regimens on finishing pig performance, stomach morphology, and carcass characteristics - De Jong, Jon A.; DeRouchey, Joel M.; Tokach, Michael D.; Dritz, Steven S.; Goodband, Robert D.; Woodworth, Jason C.; Allerson, M. W. (My University, 2017)
A total of 2,100 pigs (PIC 327 x 1050; initially 31.2 kg BW) were used in a 118-d trial to determine the effects of pellet or meal feeding regimens on finishing pig growth performance, stomach morphology, and carcass characteristics. Pens of pigs were balanced by initial BW and randomly allotted to 1 of 6 dietary treatments (14 pens/treatment with 25 pigs/pen). Pens were sorted by gender allowing for 7 barrow pens and 7 gilt pens per treatment. The same corn-soybean meal-based diets containing 15% dried distillers' grains with solubles were used for all treatments and fed in 5 phases. Phases were fed from d 0 to 28, 28 to 56, 56 to 84, 84 to 98, and 98 to 118. The 6 treatments included a meal or pelleted diet fed from d 0 to 118, a meal diet fed from d 0 to 70 followed by pellets from d 70 to 118, a pelleted diet fed from d 0 to 70 followed by a meal diet from d 70 to 118, or pellets and meal rotated every 2 wk starting with meal or pellets. On d 110, 4 pigs from each pen were harvested and stomachs collected, from which a combined ulcer and keratinization score was determined for each pig. Overall, there were no differences in ADG across feeding regimens. Pigs fed meal throughout had the greatest (P < 0.05) ADFI, whereas pigs fed pellets throughout had the lowest (P < 0.05), with all other treatments intermediate (P < 0.05). Pigs fed pelleted diets throughout had the greatest (P < 0.05) G: F, whereas pigs fed meal throughout had the worst G: F (P < 0.05), with all other treatments intermediate (P < 0.05). When pelleted diets were fed for the last 58 d or for the entire trial, the incidence of ulceration and keratinization increased (P < 0.05), whereas pigs fed meal for the last 58 d had a lower incidence (P < 0.05), with all other treatments intermediate (P < 0.05). Feeding pellets throughout increased (P < 0.05) the number of pigs removed per pen compared with all other treatments. Pig removals were determined by an on-site farm manager when pigs were at risk due to weight loss, health, or animal welfare concerns and needed to be separated from the general population. There were no differences for any carcass characteristics measured including HCW, carcass yield, backfat depth, loin depth, and percentage lean. In conclusion, feeding pelleted diets improved G: F but increased stomach ulceration and pig removals; however, rotating pellets and meal diets provided an intermediate G: F response and moderated stomach ulcerations compared with feeding only pellets.
Citation: De Jong, J. A., DeRouchey, J. M., Tokach, M. D., Dritz, S. S., Goodband, R. D., Woodworth, J. C., & Allerson, M. W. (2016). Evaluating pellet and meal feeding regimens on finishing pig performance, stomach morphology, and carcass characteristics. Journal of Animal Science, 94(11), 4781-4788. doi:10.2527/jas2016-0461
Keywords: Finishing Pig; Growth; Meal; Pellet; Stomach Ulcer; Particle-Size